Fact of Low Hemoglobin and Packed Cell Volume in Pregnant Women are at a Stand Still (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):4-7.The abstract of this article is available on the PubMed website